Disciplinary values in legal discourse - Ruth Breeze (Ibérica, 2011)
The last 20 years have seen increasing interest in the way in which meaning is made in different professional and academic disciplines. Central to this issue is the notion of disciplinary values, that is, qualities which define what is prized or stigmatised by different professional communities. In the present paper, the notion of disciplinary values is used to examine the way legal writers communicate meaning in different genres. To this end, six adjective/adverb sets which have a prominent place in legal discourse ("clear/ly", "important/ly", "reasonable/ly", "appropriate/ly", "correct/ly" and "proper/ly") are identified. Their collocates and semantic preferences are studied in four 500,000-word corpora consisting of texts from the area of commercial law: academic journal articles, case law, legislation, and legal documents. Although the frequency and use of "clear/ly" and "important/ly" appear not to differ greatly from those found in other corpora of written and academic written texts such as the British National Corpus (BNC) and the British Academic Written English corpus (BAWE), "reasonable/ly", "appropriate/ly", "correct/ly" and "proper/ly" were found to be salient in some or all of the subcorpora. The reasons for this are then analysed within the framework of disciplinary values. These words appear to convey attributes that have particular importance in the legal profession, reflecting disciplinary values that cross the boundaries between various written genres.